2012
DOI: 10.12712/rpca.v6i1.110
|View full text |Cite
|
Sign up to set email alerts
|

Desafios do Ensino Superior para Estudantes de Escola Pública: um Estudo na UFLA

Abstract: RESUMOEste trabalho busca compreender os desafios enfrentados por estudantes vindos de escolas públicas, por meio da análise, em específico, do curso de Administração da Universidade Federal de Lavras, entre 2005 a 2010. Para tanto, utilizou-se de uma abordagem predominantemente qualitativa, a partir de questionários semi-estruturados e de um grupo focal. Os resultados obtidos revelaram que a formação do estudante de escola pública é permeada por dificuldades, dentre as quais, destacam-se a falta de estrutura … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
24

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 1 publication
0
3
0
24
Order By: Relevance
“…This reality can be explained by different reason which need to be investigated by more specific and deeper studies for each context. However, from the researches already done about the theme in Brazil (Alvarenga et al, 2012;Caôn e Frizzo, 2010;Costa & Dias, 2015;Gatti & Barreto, 2009;Louzano et al, 2010;Rosa, 2014), we can infer that some of these reasons lie in the fragility of K12 education that, also for different reasons, does not offer a solid base which would guarantee students' permanence in the undergraduate courses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reality can be explained by different reason which need to be investigated by more specific and deeper studies for each context. However, from the researches already done about the theme in Brazil (Alvarenga et al, 2012;Caôn e Frizzo, 2010;Costa & Dias, 2015;Gatti & Barreto, 2009;Louzano et al, 2010;Rosa, 2014), we can infer that some of these reasons lie in the fragility of K12 education that, also for different reasons, does not offer a solid base which would guarantee students' permanence in the undergraduate courses.…”
Section: Resultsmentioning
confidence: 99%
“…As beforementioned, governmental actions such as Reuni, Fies, and Law nº 12.711/2012, contributed to a greater democratization on the access to Higher Education, as young people, especially those from low-income families, and most of them from public schools, had better opportunities to compete for places in the universities with students from higher social classes, who mostly studied in private schools and had access to an education that, according to Alvarenga et al (2012), prepared them to be admitted in good public universities.…”
Section: Resultsmentioning
confidence: 99%
“…Alvarenga et al (2012) also identified a lack of prerequisites with students from a public university, graduates of public schools. The ProUni scholarship effort has been pointed out as a key aspect to getting good grades and not losing the scholarship (ESTÁCIA, 2009;FELICETTI, 2011;MONGIN, 2010;ROCHA, 2008;SENA, 2011).…”
Section: Theoretical Contributionmentioning
confidence: 99%
“…Segundo Alvarenga et al (2012), as escolas públicas não divulgam e nem despertam interesse nos alunos pelas Universidades, além de criarem uma cultura desmotivadora que leva os estudantes a não tentarem o vestibular por acreditarem serem incapazes de concorrer com aqueles oriundos de escola privada Assim, para os estudantes de escola pública, o acesso ao ensino superior não é entendido como processo natural de continuidade dos estudos (ZAGO, 2006). É importante ressaltar, ainda, que a fase da vida na qual os jovens se encontram no ensino médio é um período conflitante, caracterizado pela diminuição do entusiasmo pelos estudos, acrescido de novos interesses, tais como o ingresso no mercado de trabalho (KRAWCZYK, 2011).…”
Section: Introductionunclassified